UJI EFEKTIFITAS EKSTRAK KUNYIT (Curcuma domestical) TERHADAP DAYA TETAS TELUR IKAN GURAMI (Osphronemus gouramy Lac.) - Muarofah Ghofur; M. Sugihartono; Jon Arfah (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
This research aims to know the effectiveness of turmeric extract (c. domestical) as anti-bacterial tetas power against egg fish gourami (o. gouramy) maintained in controlled inside the Aquarium. This research was carried out in the installation of ornamental fish Orchid Garden, Jambi.Egg test used in this research is egg fish gourami (o. gouramy) obtained from BBAT Gelam River as much as 1200 eggs with dense stocking 100 rounds/container. The containers used in the immersion uses the jar with a volume of 1 liter of water for 20 minutes, then moved into an aquarium sized 50x40x40 cm as many as 12 fruit, filled water as much as 20 litres/containers and each equipped with aeration and water heater.The design used was Complete Random Design (RAL) with 4 treatment with turmeric extract is concentration of awarding 0 ml/l, 5 ml/l, 10 l, and ml/15 ml/l each with three times in Deuteronomy. The parameters observed were power tetas egg and Larval survival. The results were analyzed with the prints, then proceed with test Duncan (DNMRT) at the 5% level.From the results of the analysis of differences range shows that yout soaking with turmeric extract shows the influence of the very real power of success against tetas egg and Larval survival of fish gourami (o. gouramy). From the results of research conducted showed that treatment with 10 ml/l concentration gave results that are highly optimized for a successful power 75% of eggs tetas whereas larval survival of 75%.Keyword : test the effectiveness of turmeric extract, eggs, fish gourami